THE USE OF SPONTANEOUS GROUP DISCUSSION (SGD) TO TEACH WRITING DESCRIPTIVE TEXT: A CASE OF THE EIGHTH GRADE STUDENTS OF SMP 1 - Reni Lestari (Universitas PGRI Semarang, 2014)
This study focuses on the use of Spontaneous Group Discussion (SGD) in writing descriptive text. The objectives of the study are (1) to find out students’ writing ability in descriptive text taught without using Spontaneous Group Discussion (SGD), (2) to find out students’ writing ability taught using Spontaneous Group Discussion, (3) to find out whether there is any significant difference of students’ writing ability in descriptive text of the eighth grade students of SMP 1 Kesesi taught without using Spontaneous Group Discussion and taught using Spontaneous Group Discussion. In this study, the researcher used true experimental design by post test control and experiment group design. The eighth grade students of SMP 1 Kesesi were the population of this study. By using cluster random sampling as a technique to take sample, the researcher chose students of VIII A and VIII B as samples. VIII A in which consisted of 36 students was chosen as experiment class. While VIII B in which consisted of 37 students was chosen as control class.Essay text was the instrument for collecting data. Post test was used by the researcher to find out whether there is any significant difference of students’ writing ability in descriptive text who given treatment trough Spontaneous Group Discussion and without using spontaneous Group Discussion as treatment.Based on data analyses, the researcher found that the mean score of experiment class was higher than the mean score of control class (79, 64 > 74, 22). In addition, the independent sample t-test of both classes showed that the result of t-test value was 2,301 and t-table on significance degree (5%) was 1, 688. It shows that t-test value was higher than t-table value (2,301 > 1, 688). By the result, the researcher concludes that there was significant difference of students’ writing ability in descriptive text taught without using Spontaneous Group Discussion and taught using Spontaneous Group Discussion.Based on the result of the study, SGD can be recommended for English teacher, the students and the readers that may be useful to be used as an effective technique for teaching learning process in descriptive text. Besides using Spontaneous Group Discussion as technique in teaching English, the teacher should be more creative so that can give variation teaching especially in writing descriptive text. For the students, they should do more practice in learning writing descriptive text so that they can master writing descriptive text.